Endoscopic ultrasound-guided creation of a transgastric fistula for the management of hepatobiliary disease in patients with Roux-en-Y gastric bypass - Ngamruengphong, Saowanee; Nieto, Jose; Kunda, Rastislav; Kumbhari, Vivek; Chen, Yen-I; Bukhari, Majidah; El Zein, Mohamad Hassan; Bueno, Renata P.; Hajiyeva, Gulara; Ismail, Amr; Chavez, Yamile Haito; Khashab, Mouen A. (Endoscopy, 2017)
Background and aims Endoscopic retrograde cholangiopancreatography (ERCP) in patients who have undergone Roux-en-Y gastric bypass (RYGB) is technically challenging. We describe our multicenter experience using lumen-apposing metal stents (LAMSs) to create an endoscopic ultrasound-guided transgastric fistula (EUS-TG) to facilitate peroral ERCP in these patients. Patients and methods Thirteen patients with RYGB who underwent EUS-TG at three tertiary centers were included. EUS was used to guide puncture of the excluded stomach from the gastric pouch or jejunum; a LAMS was placed across the transgastric fistula. ERCP was performed via a duodenoscope passed through the LAMS.Results The technical success of EUS-TG was 100 % (13/13). ERCP through the LAMS was successful and clinical success was achieved in all patients. LAMS dislodgement during ERCP occurred in two patients and the stent was successfully repositioned without sequelae. After removal of the LAMS, the fistula was closed in 92 % of patients, either by endoscopic closure devices or argon plasma coagulation. None of the patients experienced procedure-related adverse events.Conclusion EUS-TG is an effective and safe method of accessing the excluded stomach and performing ERCP in patients with RYGB.